Budaya dan Modernisasi: Pergulatan Orang Mentawai Dalam Memperkuat Identitas Budaya - Erwin, Erwin; Irwandi, Ade; Ermayanti, Ermayanti; Indrizal, Edi (Universitas Padjadjaran, 2024)
This study examines the Mentawai struggle to perform their cultural identity in the middle of hegemonic influence development and policies which contradicts their cultural identity and which gives rise to a cultural crisis. Critical anthropology's view shows that humans have the potential to create creativity and customisation. However, the Mentawai are limited and suppressed by social factors, cultural conditions, and exploited by the authorities. It means that the reality as Mentawai is not created by nature, but by humans, who have the power to manipulate the condition and patent the meaning that suits his own mind that is full of conflict, illusion, and distortion. Mentawai are in a ‘false consciousness’ that modernisation helps them to see the better world and have consciously stuttered (cultural backwardness) from that subconscious condition. Culture is deliberately clashed with modernisation in various elements of life such as in customs, language, food, and lifestyle. Furthermore, the generalization of development programmes also intervenes to sharpen the domination to narrow down the socio-cultural life of the Mentawai. However, they are not rigid. They practice cultural tactics (cultural meaning) in order to keep up with modernisation. They also consider modernisation and globalization as ‘interaction spaces’ in which the contestation of various elements of human life take place.